2009
DOI: 10.1124/dmd.108.026484
|View full text |Cite
|
Sign up to set email alerts
|

Generation of the Human Metabolite Piceatannol from the Anticancer-Preventive Agent Resveratrol by Bacterial Cytochrome P450 BM3

Abstract: ABSTRACT:In recent studies, the wild-type and mutant forms of cytochrome P450 (P450) BM3 (CYP102A1) from Bacillus megaterium were found to metabolize various drugs through reactions similar to those catalyzed by human P450 enzymes. Therefore, it was suggested that CYP102A1 can be used to produce large quantities of the metabolites of human P450-catalyzed reactions. trans-Resveratrol (3,4,5-trihydroxystilbene), an anticancer-preventive agent, is oxidized by human P450 1A2 to produce two major metabolites, picea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 75 publications
(56 citation statements)
references
References 24 publications
0
55
1
Order By: Relevance
“…CYP102A1 mutants were found to generate human drug metabolites by oxidizing various drugs, including clozapine (Damsten et al, 2008), diclofenac (Damsten et al, 2008), acetaminophen (Damsten et al, 2008), 3,4-methylenedioxymethylamphetamine (Stjernschantz et al, 2008), dextromethorphan (Stjernschantz et al, 2008), phenacetin , verapamil (Sawayama et al, 2009), and astemizole (Sawayama et al, 2009). CYP102A1 mutants can also oxidize several human P450 substrates, including 7-ethoxycoumarin (Kim et al, 2008b), coumarin (Park et al, 2010), chlorzoxazone (Park et al, 2010), and resveratrol (Kim et al, 2009), to generate human metabolites.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CYP102A1 mutants were found to generate human drug metabolites by oxidizing various drugs, including clozapine (Damsten et al, 2008), diclofenac (Damsten et al, 2008), acetaminophen (Damsten et al, 2008), 3,4-methylenedioxymethylamphetamine (Stjernschantz et al, 2008), dextromethorphan (Stjernschantz et al, 2008), phenacetin , verapamil (Sawayama et al, 2009), and astemizole (Sawayama et al, 2009). CYP102A1 mutants can also oxidize several human P450 substrates, including 7-ethoxycoumarin (Kim et al, 2008b), coumarin (Park et al, 2010), chlorzoxazone (Park et al, 2010), and resveratrol (Kim et al, 2009), to generate human metabolites.…”
Section: Discussionmentioning
confidence: 99%
“…The fusion of these two enzymatic activities makes soluble CYP102A1 an ideal model for mammalian, particularly human, P450 enzymes. In recent studies, CYP102A1 mutants engineered through rational design or directed evolution were reported to produce human drug metabolites (Kim et al, 2008b(Kim et al, , 2009Sawayama et al, 2009;Park et al, 2010). In addition, CYP102A1 is a versatile monooxygenase with a demonstrated ability to catalyze a diversity of substrates and an established relevance to biotechnology (Urlacher and Eiben, 2006;Yun et al, 2007;Julsing et al, 2008 and references within).…”
Section: Introductionmentioning
confidence: 99%
“…The direct use of human cytochrome P450 is limited by the need of a redox partner and the poor stability and activity. However, bacterial counterparts such as cytochrome P450 BM3 (CYP102A1) from Bacillus megaterium, can be directly used [3] or engineered to metabolise drugs and to produce the same metabolites as the human enzymes [4][5][6][7][8][9][10][11][12][13][14]. This protein is a selfsufficient fatty acids monoxygenase containing a NADPH-dependent reductase (BMR) and a P450 catalytic domain (BMP) fused in a single polypeptidic chain [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…It has been observed that even low doses (such as consumed in the common diet) of resveratrol shows cardio-protective activity [26].…”
Section: Resveratrol In Cardiovascular Protectionmentioning
confidence: 99%